KEKOSONGAN HUKUM JASA USAHA KEPELABUHAN AKIBAT PEMBATASAN OBYEK RETRIBUSI DAERAH - Sukardi ,; Dri Utari Christina Rahmawati (Yuridika, 2014)
Local autonomy based on the Act No. 22 Year 1999 about Local Autonomy (amended by the Act No. 32 Year 2004 about Local Governance) has delivered broad autonomy to local governance to add its local revenue through cllection, local tax and local retribution. The impementation of local autonomy should be in the line with the unitary state of Indnesia as attached in the Constitution 1945 and other supporting rules in legislation. The formation of Local Procedures by Local Governance should not only partially benefit local governance but also they need pay attention to their functions in public services. Retribution withdrawal by Gresik Regency towards 8 ports for own interests should be based on the hierarchy of the regulations. It means that in the art of the Local Rules should not be contrary to the higher rules.Keywords: local autonomy, retriution, local rules, public service.